2019
DOI: 10.1080/02813432.2019.1569427
|View full text |Cite
|
Sign up to set email alerts
|

Giving callers the option to bypass the telephone waiting line in out-of-hours services: a comparative intervention study

Abstract: Objective: Acute out-of-hours (OOH) healthcare is challenged by potentially long waiting time for callers in acute need of medical aid. OOH callers must usually wait in line, even when contacting for highly urgent or life-threatening conditions. We tested an emergency access button (EAB), which allowed OOH callers to bypass the waiting line if they perceived their health problem as severe. We aimed to investigate EAB use and patient characteristics associated with this use. Design: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 20 publications
2
22
0
Order By: Relevance
“…As found in this study, Denmark has a relatively high number of OOH-PC contacts per inhabitants (approximately 500/1000) [11,26] compared with other countries with similar health care organizations (ranging from around 150-410/1000) [27][28][29], whereas the level of EMS contacts (100/1000) is more alike [1,30,31]. In the present study, the number of subsequent hospital contacts depending on type of OOH service differed, which was to be expected when comparing EMS and OOH-PC.…”
Section: Comparison With Literaturesupporting
confidence: 59%
“…As found in this study, Denmark has a relatively high number of OOH-PC contacts per inhabitants (approximately 500/1000) [11,26] compared with other countries with similar health care organizations (ranging from around 150-410/1000) [27][28][29], whereas the level of EMS contacts (100/1000) is more alike [1,30,31]. In the present study, the number of subsequent hospital contacts depending on type of OOH service differed, which was to be expected when comparing EMS and OOH-PC.…”
Section: Comparison With Literaturesupporting
confidence: 59%
“…An assessment of nonrespondents showed that non-respondents were similar to participants with regard to age, gender and triage response, but selection bias cannot be ruled out. Yet, very worried callers might not have wished to participate, however this fraction is supposedly limited as only a small low number of callers (< 4%) used an emergency access button to bypass the telephone waiting line in a similar study [33]. Moreover, potential severe illnesses which were treated or refuted in less than 24 h were not included in the endpoint, which might have drawn the results in the direction of an underestimation of the association between DOW and hospital admission.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…MH-1813 carry out home visits, whereas the clinic consultations take place in hospital emergency departments. 23 As well as answering direct calls, the physicians also act as consultants for the nurses. Both GPC and MH-1813 were considered OOH-PC services in this study.…”
Section: Settingmentioning
confidence: 99%